2015
DOI: 10.1002/ppap.201500106
|View full text |Cite
|
Sign up to set email alerts
|

Plasma‐Assisted Fabrication of Fe2O3Co3O4 Nanomaterials as Anodes for Photoelectrochemical Water Splitting

Abstract: Nanocomposite Fe2O3Co3O4 photoanodes for photoelectrochemical H2O splitting were prepared by a plasma‐assisted route. Specifically, Fe2O3 nanostructures were grown by plasma enhanced‐chemical vapor deposition, followed by cobalt sputtering for different process durations. The systems were annealed in air after, or both prior and after, sputtering of Co, to analyze the treatment influence on functional performances. The interplay between processing conditions and chemico‐physical features was investigated by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
58
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(68 citation statements)
references
References 54 publications
10
58
0
Order By: Relevance
“…For the composite samples, no additional signals related to crystalline Fe 2 O 3 or WO 3 or mixed Zn‐Fe‐O/Zn‐W‐O phases could be observed. In line with previous works on multicomponent oxide nanosystems obtained by analogous routes, this result could be related to the low Fe 2 O 3 /WO 3 loading, as confirmed by transmission electron microscopy (TEM) data (see below and Figure ), and suggested that the adopted processing conditions were mild enough to avoid significant structural alterations of the pristine ZnO matrix. The main difference for ZnO‐Fe 2 O 3 and ZnO‐WO 3 systems with respect to bare ZnO was the slightly lower I (002) / I (101) intensity ratio (Figure S1, Supporting Information).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…For the composite samples, no additional signals related to crystalline Fe 2 O 3 or WO 3 or mixed Zn‐Fe‐O/Zn‐W‐O phases could be observed. In line with previous works on multicomponent oxide nanosystems obtained by analogous routes, this result could be related to the low Fe 2 O 3 /WO 3 loading, as confirmed by transmission electron microscopy (TEM) data (see below and Figure ), and suggested that the adopted processing conditions were mild enough to avoid significant structural alterations of the pristine ZnO matrix. The main difference for ZnO‐Fe 2 O 3 and ZnO‐WO 3 systems with respect to bare ZnO was the slightly lower I (002) / I (101) intensity ratio (Figure S1, Supporting Information).…”
Section: Resultssupporting
confidence: 88%
“…In this broad scenario, an attractive option involves the use of Fe 2 O 3 and WO 3 as functional activators of ZnO systems for the fabrication of vis‐light absorbing photoanodes. In particular, Fe 2 O 3 , an abundant and cheap oxide with a narrow band gap ( E G = 2.2 eV), has gained a considerable attention, but its sluggish oxygen evolution kinetics, low carrier lifetime, and short exciton diffusion length limit the resulting functional performances . Another attractive material not only for solar water splitting, but also for environmental remediation, is WO 3 , which possesses an appreciable photostability and a favorable band gap ( E G = 2.8 eV) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower slope reported for the BiVO 4 -Zr samples is connected to an increasei nt he surfacea rea as showni nF igure 2, rather than to an increasei nd onor density.T he material roughnessi sf urther increasedf or the BiVO 4 -Zr-Fe sample, which can explain the lowest slope in the Mott-Schottky plot of Figure SI6, as ac onsequence of the Fe 2 O 3 nanoparticle decoration and/ort he ZrO 2 morphological rearrangement on top of BiVO 4 photoanode under the second annealing. [24] The calculated flat band potentials (V fb )a nd donor densities (N D )a re collected in Ta ble SI2. No significant changes are obtained for the electronic properties of BiVO 4 upon Zr and Fe additions, as reflectedi nt he charge separation yield in Figure 5a.…”
mentioning
confidence: 99%
“…Schäfer et al reported that the FeO(OH)/Fe 2 O 3 ratio has an important effect on the water‐splitting performance . Many other methods have been exploited to improve the water‐splitting performance of hematite‐based PEC cells, for example, doping elements (Mn, Sn, Ti, Si, F, Mg, Zn, Mo, Cr, and others), or decorating the hematite with WO 3 , Co 3 O 4 , Co‐Pi, IrO 2 , Ga 2 O 3 , ZnFe 2 O 4 , ZnO, ITO, Al 2 O 3 , SnO 2 , TiO 2 , or other materials . The enhanced performances resulting from these experiments can be attributed to improved UV‐Vis absorption and modification of surface states .…”
Section: Introductionmentioning
confidence: 99%